Higher urate in LRRK2 mutation carriers resistant to Parkinson disease. Issue 4 (3rd March 2019) - Bakshi, Rachit; Macklin, Eric A.; Logan, Robert; Zorlu, Musab M.; Xia, Ning; Crotty, Grace F.; Zhang, Ellen; Chen, Xiqun; Ascherio, Alberto; Schwarzschild, Michael A.
Abstract : Objective: LRRK2 mutations, the most common genetic cause of Parkinson disease (PD), display incomplete penetrance, indicating the importance of other genetic and environmental influences on disease pathogenesis in LRRK2 mutation carriers. The present study investigates whether urate, an antioxidant, Nrf2 activator, and inverse risk factor for idiopathic PD, is one such candidate biomarker of PD risk modulation in pathogenic LRRK2 mutation carriers. Methods: Banked plasma samples or urate levels were obtained for 3 cohorts of age‐ and sex‐matched subjects with and without a known LRRK2 mutation in PD and unaffected controls to conduct a pilot study of 192 subjects from the LRRK2 Cohort Consortium (LCC) and 2 validation studies of 380 additional subjects from the LCC and 922 subjects from the Parkinson's Progression Markers Initiative. Urate levels were compared by multiple regression between subjects with and without a PD diagnosis conditional on LRRK2 status, controlling for age and sex. Results: Nonmanifesting LRRK2 mutation carriers had significantly higher levels of urate than those who developed PD in each of the 3 independent cohorts. A meta‐analysis demonstrated an adjusted mean difference of 0.62 mg/dL ( p < 0.001), with similar results for separate assessments of women ( p < 0.02) and men ( p < 0.001). A 2 mg/dL increment in urate concentration decreased the odds of having PD by approximately 50% (odds ratio = 0.48, p = 0.004). Interpretation: These findings identify and substantiate urate as a biomarker of resistance to PD among LRRK2 mutation carriers. Ann Neurol 2019;85:593–599